Musicolinguistic Analysis of some Selected Yorùbá and Igbo Folk Songs (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2025)
Studies on musicolinguistics have received scholarly attention with a lot of them showing the interrelatedness of language and music. However, very limited studies have analysed the incorporation of musicolinguistics with Yoruba and Igbo folk songs combined to examine the interconnectivities existing between linguistics and music. This study, therefore, x-rays the musicolinguistic analysis of some selected Yorùbá and Igbo folk songs. The study adopts a qualitative research design to draw on the effect of language on music. Sleeper's (2018) integration of musical data into linguistics provides a framework for analyses in this study. Also, data for the study are drawn from the selected Yorùbá and Igbo folk songs: “L'abe Igi Orombo”, “Olúrónbí” and “Uri Oma”. Findings from the study reveal that folk songs are used to preserve Yorùbá and Igbo linguistic clarity while elevating their artistic and cultural expression. Through the careful balance of text and melody, these folk songs demonstrate how music functions as an extension of language, reinforcing meaning, identity, and cultural continuity. The study contributes to the field of musicolinguistics and African folk songs.
Keywords: Musicolinguistics; music; linguistics; folk songs; interconnectivities